Pengaruh Game Online terhadap Motivasi Belajar Siswa Sekolah Dasar - Waqi, Anisrul; Nisa, Sahrun (Lembaga Yasin AlSys, 2024)
Online games are application devices that have interesting features that can be played by all groups, including children. Playing online games excessively has a negative impact on children, one of which is reduced motivation to learn. The aim of this research is to find out how online games influence elementary school students' learning motivation. This research uses a literature study method where the researcher reviews existing articles or journals that are relevant or related to the topic. The results of this research prove that playing online games excessively has a big influence on elementary school students' learning motivation. The more often a child plays online games, the more his motivation to learn decreases.